Cidades inteligentes: uma alternativa para minimizar os problemas enfrentados na busca pelo meio ambiente ecologicamente equilibrado - Sabio, Thais Fernanda (2023)
The concept of Smart Cities has become paramount in contemporary society, attracting international attention due to its potential to address pressing environmental challenges and improve quality of life amidst rapidly growing urban populations. This paper delves into the study of sustainable development and the pursuit of an ecologically balanced environment in alignment with numerous guiding legal principles aimed at prevention and remediation. A Smart City can be defined through various criteria, and this work examines their implementation in light of minimizing environmental issues prevalent in society, thereby fostering an ecologically balanced environment alongside socioeconomic growth. The concept of a Smart City is still evolving, yet the evaluation of a city's 'smartness' commonly involves aspects of mobility and accessibility, environment, urban planning, technology and innovation, health, safety, education, entrepreneurship, energy, governance, and economics. Legislation provides the groundwork for a municipality to evolve into a Smart City by laying out guiding principles, objectives, and priorities, and potentially establishing dedicated working groups for this purpose. The critical role of regulatory agencies in regulating, controlling, and supervising the provision of public services is also discussed. Employing an analytical method, this dissertation undertakes a study of bibliographical references to explore the identified problem further. Given the array of environmental issues faced by Brazil, there is an urgent need to mitigate these challenges to realize sustainability and an ecologically balanced environment. This need extends to ensuring citizens' basic rights because developing Smart Cities necessitates a multisectoral perspective, encompassing social, environmental, and economic considerations.